THE PREVALENCE OF ANKYLOSING SPONDYLITIS AMONG UNIVERSITY STUDENTS - Ayşe Gürler,; Ece Kaptanoğlu,; Hasan Elden,; Vedat Nacitarhan,; Sami Hizmetli, (Archives of Rheumatology, 2004)
Ankylosing spondylitis is a common form of seronegative spondyloarthropathies which may lead to disability. However, there are not satisfactory data concerning the prevalence in our country just as in many others. So we aimed at searching the prevalence of ankylosing spondylitis among our university students. A sample of 712 cases representing 10161 students attending to Cumhuriyet University were given a questionnaire form and those 74 students answered positively were invited for clinical and radiological examination. Classification of ankylosing spondylitis was made according to the modified New York criteria. The prevalence and sex-specific (male) prevalence of ankylosing spondylitis among the university students were found to be 0.14% and 0.24%, respectively.